Public management and the recovery of the Historic Center of Lima. Case: Grau, Piérola and Abancay avenues, and Ancash and Huánuco streets, 2018 - GARCIA SEGOVIA, MARIA EUGENIA (2020)
The objective of the study was to determine how public management is related to the recovery of the Historic Center of Lima. Various empirical sources indicate that the loss or improper use of the built cultural heritage, together with the deficient control of the administrating authorities, contribute to its deterioration. The research was of a non-experimental design, of a descriptive correlational type and of a mixed approach. A non-probabilistic sample was used, made up of residents and economic agents who responded to a questionnaire, as well as functions and technicians of the Metropolitan Municipality of Lima. The results show that there is a correlation of 0.73, which reflects a direct, positive and high relationship, finding significance between the variables studied, since p. value = 0.000 <α 0.05. Destruction of heritage and institutional disarticulation of the Historic Center of Lima, its complex and abundant regulations, and the lack of knowledge about its importance, represent the synthesis of the inadequate actions of public management for the recovery of the Historic Center of Lima.